2015 American College of Rheumatology Workforce Study and Demand Projections of Pediatric Rheumatology Workforce, 2015–2030. Issue 3 (2nd February 2022) - Correll, Colleen K.; Ditmyer, Marcia M.; Mehta, Jay; Imundo, Lisa F.; Klein‐Gitelman, Marisa S.; Monrad, Seetha U.; Battafarano, Daniel F.
Abstract : Objective: To describe the character and composition of the 2015 pediatric rheumatology workforce in the US, evaluate current workforce trends, and project future supply and demand of the pediatric rheumatology workforce through 2030. Methods: The American College of Rheumatology created the workforce study group to study the rheumatology workforce. The workforce study group used primary and secondary data to create a representative workforce model. Pediatric rheumatology supply and demand was projected through 2030 using an integrated data‐driven framework to capture a more realistic clinical full‐time equivalent (FTE) and produce a better picture of access to care issues in pediatric rheumatology. Results: The 2015 pediatric rheumatology workforce was estimated at 287 FTEs (300 providers), while the estimated excess demand was 95 (33%). The projected demand will continue to increase to almost 100% (n = 230) by 2030 if no changes occur in succession planning, new graduate entrants into the profession, and other factors associated with the workforce. Conclusion: This study projects that the pediatric rheumatology workforce gap will continue to worsen significantly from the 2015 baseline, and by 2030 the demand for pediatric rheumatologists will be twice the supply. Innovative strategies are needed to increase the workforce supply and to improve access to care.